Making surveillance states: transnational histories - Heynen, Robert; Van der Meulen, Emily (University of Toronto Press, 2019)
"Making Surveillance States: Transnational Histories opens up new and exciting perspectives on how systems of state surveillance developed over the nineteenth and twentieth centuries. Taking a transnational approach, the book challenges us to rethink the presumed novelty of contemporary surveillance practices, while developing critical analyses of the ways in which state surveillance has profoundly shaped the emergence of contemporary societies. Contributors engage with a range of surveillance practices, including medical and disease surveillance, systems of documentation and identification, and policing and security. These approaches enable us to understand how surveillance has underpinned the emergence of modern states; sustained systems of state security; enabled practices of colonial rule; perpetuated racist and gendered forms of identification and classification; regulated and policed migration; shaped the eugenically inflected medicalization of disability and sexuality; and contained dissent. While surveillance is thus bound up with complex relations of power, it is also contested. Emerging from the book is a sense of how state actors understood and legitimized their own surveillance practices, as well as how these practices have been implemented in different times and places. At the same time, contributors explore the myriad ways in which these systems of surveillance have been resisted, challenged, and subverted."--